Shift schedules and circadian preferences: the association with sleep and mood - Ahn, Jihye; Yeo, Hyewon; Lee, Somi; Hwang, Yunjee; Jeon, Sehyun; Kim, Seog Ju (Frontiers in Public Health, 2024)
Object We explored the circadian preferences of non-shift workers (non-SWs) and various types of shift workers (SWs), and the associations of these preferences with sleep and mood. Methods In total, 4,561 SWs (2,419 women and 2,142 men aged 37.00 ± 9.80 years) and 2,093 non-SWs (1,094 women and 999 men aged 37.80 ± 9.73 years) completed an online survey. Of all SWs, 2,415 (1,079 women and 1,336 men aged 37.77 ± 9.96 years) reported regularly rotating or fixed schedules (“regular SWs”), and 2,146 (1,340 women and 806 men aged 36.12 ± 9.64 years) had irregular schedules (“irregular SWs”). Of the regular SWs, 2,040 had regularly rotating schedules, 212 had fixed evening schedules, and 163 had fixed night schedules. All participants completed the Morningness-Eveningness Questionnaire (MEQ) exploring circadian preferences, the short form of the Center for Epidemiological Studies-Depression Scale (CES-D) evaluating depression, the Insomnia Severity Index (ISI), and the Epworth Sleepiness Scale (ESS). Results Compared to non-SWs, SWs had lower MEQ scores, i.e., more eveningness, after controlling for age, gender, income, occupation, and weekly work hours (F = 87.97, p < 0.001). Irregular SWs had lower MEQ scores than regular SWs (F = 50.89, p < 0.001). Among regular SWs, the MEQ scores of fixed evening and fixed night SWs were lower than those of regularly rotating SWs (F = 22.42, p < 0.001). An association between the MEQ and ESS scores was apparent in non-SWs (r = −0.85, p < 0.001) but not in SWs (r = 0.001, p = 0.92). Conclusion SWs exhibited more eveningness than non-SWs; eveningness was particularly prominent in SWs with irregular or fixed evening/night shifts. Eveningness was associated with sleepiness only in non-SWs, but not in SWs.